A BEHAVIORAL MODEL INTERPRETATIVE MATERIAL THERMOELASTIC WEBBED - CHUQUILIN TERÁN, C. (1998)
Molecular networks may be considered as elastic fluids, the conformational abilities of which are adecuately characterized with the aid of the model of a Van der Waals conformational gas with weak interactions. The internal properties are submitted to the conditions of internal equilibrium, thus, having their changes uniquely related to the global transformations of the network upon deformation. The global properties are at least determining the limits of stability which are expressed in the Van der Waals approach by formulating of a reduced equation of state of real networks. lt will be discussed on hand of thermo-elastic measurements and its quantitative description what is in need for a full and self-containing phenomenological description of molecualr networks.